Uji Aktivitas Antibakteri dan Analisis KLT-Bioautografi Ekstrak Etanol Daun Situduh Langit (Erigeron sumatrensis Retz) Terhadap Bakteri Escherichia coli - Saepudin, Syumillah; Kartikawati, Endah; Herliyani, Widya (LP4M STIKes Karsa Husada Garut, 2024)
Introduction: Situduh langit (Erigeron sumatrensis Retz.) is a plant with medicinal benefits for mouthwash, headaches, muscle pain, canker sores, blood pressure regulation, and acne treatment. It also has antimicrobial activity. Secondary metabolites like saponins and flavonoids in situduh langit can treat diarrhea. Method: This study aims to determine the concentration and TLC-Bioautography profile of ethanol extract from situduh langit leaves for inhibiting Escherichia coli. The leaves were extracted using the maceration method with 70% ethanol. The antibacterial activity of the ethanol extract at concentrations of 6.5%, 12.5%, 25%, and 50% was tested using the disc diffusion method. TLC-Bioautography identified the compounds with antibacterial activity. Results: ANOVA analysis showed normal and homogeneous data with a significance value of 0.000 < 0.05. The 6.5% concentration had an average inhibition of 6.0±0.00; 12.5% had 6.23±0.24; 25% had 6.77±0.89. These showed the smallest effect on inhibiting Escherichia coli growth. The 50% concentration had an average inhibition of 7.71±1.17, showing the greatest effect. TLC-Bioautography showed Rf values of 0.97; 0.92; 0.67; 0.60; 0.31; 0.21 and 0.14, with no clear zones forming around the media. Conclusion: The leaf extract of situduh langit has antibacterial activity against Escherichia coli at a 50% concentration with a moderate category, and TLC-Bioautography analysis of the ethanol extract did not form clear zones around the media.